Morus alba Stem Extract Suppresses Matrix Metalloproteinases (MMP)-1, MMP-9, and Tissue Inhibitors of Metalloproteinase (TIMP)-1 Expression via Inhibition of IκBα Degradation Induced by Porphyromonas gingivalis LPS Signal in THP-1 Cells - Yiemwattana, Ichaya; Kaomongkolgit, Ruchadaporn; Wirojchanasak, Sodsi; Chaisomboon, Niratcha (European Journal of Dentistry, 2019)
Objectives The aim of this study is to evaluate the inhibitory effects of M. alba stem extract (MSE) on the expression of matrix metalloproteinases (MMP)-1, MMP-9, and tissue inhibitors of metalloproteinase (TIMP)-1 in Porphyromonas gingivalis lipopolysaccharide (LPS)-activated-acute monocytic leukemia cell line (THP-1).Materials and Methods THP-1 cells were treated with noncytotoxic concentrations of MSE combined with 1 µg/mL of P. gingivalis LPS. The mRNA levels of MMP-1, MMP-9, and TIMP-1 were evaluated via quantitative real-time polymerase chain reaction. The secreted proteins in the culture media were detected by enzyme-linked immunosorbent assay. The degradation of inhibitor of kappa B-alpha (IκBα) protein was tracked by Western blotting.Statistical Analysis Comparisons in experiments were analyzed with analysis of variance followed by Tukey honestly significant difference comparison test.ResultsTwenty and 40 µg/mL of MSE significantly downregulated MMP-1 and MMP-9 genes and protein expression but upregulated the gene expression of TIMP-1 (p < 0.05). P. gingivalis LPS induced degradation of IκBα, while addition of MSE (20 and 40 µg/mL) increased IκBα cytosolic levels. MSE was able to suppress the P. gingivalis LPS-induced MMPs expression and also increased the gene expression of TIMP-1 via the inhibition of the cytoplasmic IκBα degradation in THP-1 cells.Conclusions The present observations suggest that MSE exerted a positive effect on the regulatory mechanism between MMPs and TIMP, which is an important implication for the therapeutic potential of MSE in periodontitis.
Keywords: matrix metalloproteinases; lipopolysaccharide; monocytes; M. alba stem extract